Smoking Bans, Cigarette Prices and Life Satisfaction - Reto Odermatt; Alois Stutzer (Center for Research in Economics, Management and the Arts (CREMA), 2015)
The consequences of tobacco control policies for individual welfare are difficult to assess, even more so when related consumption choices challenge people's willpower. We therefore evaluate the impact of smoking bans and cigarette prices on subjective well-being by analyzing data for 40 European countries and regions between 1990 and 2011. We exploit the staggered introduction of bans and apply an imputation strategy to study the effect of anti-smoking policies on people with different propensities to smoke. We find that higher cigarette prices reduce the life satisfaction of likely smokers. Overall, smoking bans are barely related to subjective well-being, but increase the life satisfaction of smokers who would like to quit smoking. The latter finding is consistent with cue-triggered models of addiction and the idea of bans as self-control devices.
Keywords: D03; D62; H25; H30; I18; 330; Smoking bans; cigarette prices; life satisfaction; addiction; self-control